2005
DOI: 10.2214/ajr.185.2.01850457
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Indirect CT Venography Versus Venous Sonography in ICU Patients

Abstract: The performance characteristics of CTV and deep venous sonography were similar when compared with a clinical standard. The results support the use of indirect CTV after CT pulmonary angiography as an alternative to sonography in the ICU population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Numerous comparative studies have shown there is approximately 97% agreement between CT venography and US (54)(55)(56)(57)(58). CT venography and US have also been shown to be equivalent in patients in the intensive care unit (59). The recently completed PIOPED II study of 711 CT venograms showed 95% concordance between US and helical CT venography (4).…”
Section: Ct Angiography Combined With Ct Venography: How When and If?mentioning
confidence: 99%
“…Numerous comparative studies have shown there is approximately 97% agreement between CT venography and US (54)(55)(56)(57)(58). CT venography and US have also been shown to be equivalent in patients in the intensive care unit (59). The recently completed PIOPED II study of 711 CT venograms showed 95% concordance between US and helical CT venography (4).…”
Section: Ct Angiography Combined With Ct Venography: How When and If?mentioning
confidence: 99%
“…Sensitivity for CTV diagnosis of DVT has ranged from 70 to 100%, specificity from 93 to 100%. 32,34,[37][38][39][40][41][42][43][44][45][46][47] Studies varied by patient population characteristics, CTV protocol used (differences in distance between slices, time delay between CTPA and pelvic and lower extremity imaging, and single-vs multirow detector CT), and their retro-versus prospective nature. When a composite gold standard was used, performance of CTV was slightly superior to that of ultrasound.…”
Section: Computed Tomography Venographymentioning
confidence: 99%
“…When a composite gold standard was used, performance of CTV was slightly superior to that of ultrasound. 47 In summary, studies using CTV as a diagnostic modality for venous thrombosis date back to the early 1980s. Indirect CTV done immediately after CTPA has good interobserver agreement.…”
Section: Computed Tomography Venographymentioning
confidence: 99%
“…PE is detected in 7-27% of patients after death and either causes or contributes to death in up to 12% of patients [4,64]. On the other hand, it is clinically and technically difficult to diagnose PE, especially in the unconscious and ventilated patient [4,65,66].…”
Section: Ct Angiography With Venous Ultrasound Is An Acceptable Altermentioning
confidence: 99%
“…On the other hand, it is clinically and technically difficult to diagnose PE, especially in the unconscious and ventilated patient [4,65,66]. Most of these critically ill patients have one or more major risk factors for VTE, such as age older than 70 years, bed rest for at least 5 days, recent surgery, trauma, burn, sepsis, cancer, chronic obstructive pulmonary disease, or congestive cardiac failure [4,64]. DVT can be found in up to 40% of ICU patients [64,66,67].…”
Section: Ct Angiography With Venous Ultrasound Is An Acceptable Altermentioning
confidence: 99%